KORELASI OBESITAS SENTRAL DAN TINGKAT VO2 MAKS PADA PRIA DI KOTA MALANG - Sofyan Noor; Rias Gesang Kinanti; Olivia Andiana (Universitas Negeri Malang, 2017)
Abstract: Abnormal fat accumulation in the stomach not only a triglyceride storage organ, but also as a producer of leptin that will effect the cardiovascular system. This study was conducted with the aim of knowing men’s VO2 max in Malang. To knowing the correlation between central obesity and VO2 max. this is a survey study. The instrument used is Bench Step Test. From the results of statistical analysis, average of VO2 max respondents which is 41.95 ml/Kg/min. Correlation waist circumference and VO2 max r = -0.462 with level of significance α = 0,1 means significance.Keyword: Central obesity, VO2 max, men’s.